Organic Phosphorus Mineralization Dominates the Release of Internal Phosphorus in a Macrophyte-Dominated Eutrophication Lake - Yu, Wei; Yang, Haiquan; Chen, Jingan; Liao, Peng; Chen, Quan; Yang, Yongqiong; Liu, Yong (Frontiers in Environmental Science, 2022)
Macrophyte-dominated eutrophication (MDE) lakes have attracted wide attention due to the high phosphorus (P) loading in sediments that poses a wide spread risk for P release and pollution management. However, because of the superior productivity characteristics, the role of organic P mineralization in sediments in the internal P loading of MDE lake is still under debate. This study investigated the release dynamic of P in the sediments of Lake Caohai, a MDE lake in southwest of China, using a combination of the modified Huffer sequential extraction method, 31P nuclear magnetic resonance spectroscopy (NMR), and composite diffusive gradient in thin films (DGT) technology. Results showed that the apparent P diffusion flux at the sediment-water interface was remarkably high, with a mean value of 0.37 mg·m−2·d−1. The phosphate ester organophosphorus components (i.e., Mono-P and Diester-P) continuously deposited and degraded in the sediments maintained the high productivity of the lake, and the mineralization process plays a critical role in the release of internal P. Although the content of inorganic P in sediment is relatively high (accounting for approximately 60% of total P), the reductive mechanism based on P-containing iron oxide/hydroxide has a low contribution to the internal P loading, as was indicated by the low release rate of P-combination iron-manganese (Fe-Mn)/iron-aluminum (Fe-Al) (BD-P and NaOH-P) and the insignificant positive correlations between DGT-labile P and DGT-labile Fe in the sediment cores. Additionally, organic P in sediments could transfer to P-combination Fe-Al/Fe-Mn. However, in severely expropriated environments, the enrichment of P-combination Fe-Al/Fe-Mn in surface sediments inhibited the mineralization of monophosphate to some degree. Taken together, this study emphasized the impact of sediment organic P loading on the release of internal P in lake, highlighting that organic P is also the valuable objects for avoiding eutrophication of MDE lakes.